Do injury-resistant runners have distinct differences in clinical measures compared with recently injured runners? - Dillon, S.; Burke, A.; Whyte, E. F.; O'Connor, S.; Gore, S.; Moran, K. A. (Medicine & Science in Sports & Exercise, 2021)
Introduction: Although lower extremity muscle strength, joint motion, and functional foot alignment are commonly used, time-efficient clinical measures that have been proposed as risk factors for running-related injuries, it is unclear if these factors can distinguish injury resistance in runners. Purpose: This study compares clinical measures, with consideration of sex, between recently injured runners (3 months to 1 yr prior), those with a high level of injury resistance who have been uninjured for at least 2 yr, and never-injured runners. Methods: Averaged bilateral values and between-limb symmetry angles of lower limb isometric muscle strength, joint motion, navicular drop, and foot posture index (FPI) were assessed in a cohort of recreational runners, and their injury history was recorded. Differences in clinical measures between injury groupings were examined, with consideration of sex. Results: Of the 223 runners tested, 116 had been recently injured, 61 had been injured >2 yr ago and were deemed to have acquired reinjury resistance, and 46 were never injured. Plantarflexion was greater in both recently injured (P = 0.001) and acquired reinjury resistance runners (P = 0.001) compared with never-injured runners. Recently injured runners displayed higher hip abduction strength compared with never-injured runners (P = 0.019, ?2 = 0.038, small effect size). There were no statistically significant differences in the remaining measures between the injury groupings. With the exception of FPI, there was no interaction between sex and injury grouping for any of the measures. Conclusion: Commonly used clinical measures of strength, joint motion, and functional foot alignment were not superior in injury-resistant runners compared with recently injured runners, questioning their relevance in identifying future injury resistance of runners.